2022
DOI: 10.1101/2022.06.29.498078
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cerebrospinal fluid and blood profiles of transfer RNA fragments show age, sex and Parkinson’s disease-related changes

Abstract: Transfer RNA fragments (tRFs) have recently been shown to be an important family of small regulatory RNAs with diverse functions. Recent reports have revealed modified tRF blood levels in a number of nervous system conditions including epilepsy, ischemic stroke and neurodegenerative diseases, but little is known about tRF levels in the cerebrospinal fluid (CSF). To address this issue, we studied age, sex and Parkinsons disease (PD) distributions of tRFs in the CSF and blood data of PD patients and healthy cont… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…Additionally, studies identified MT-tRFs as key regulators in nuclear-mitochondrial communication 90 , which is dysfunctional in many neurodegenerative diseases, including AD. Notably, our finding of an association between tRFs of mitochondrial origin that carry motifs complementary to those of cholinergic transcripts, resemble the enrichment in sequence-based motifs to cholinergic transcripts in MT-tRFs from the cerebrospinal fluid (CSF) and blood of donors with Parkinson's Disease (PD) 91 . These results suggest that the mitochondrial damage seen in neurodegenerative disorders such as PD 92 and AD 15 is linked to failed regulation of cholinergic targets by CholinotRFs, and potentially to a broader cholinergic and mitochondrial linked defect in sncRNAs at large.…”
Section: Discussionmentioning
confidence: 55%
“…Additionally, studies identified MT-tRFs as key regulators in nuclear-mitochondrial communication 90 , which is dysfunctional in many neurodegenerative diseases, including AD. Notably, our finding of an association between tRFs of mitochondrial origin that carry motifs complementary to those of cholinergic transcripts, resemble the enrichment in sequence-based motifs to cholinergic transcripts in MT-tRFs from the cerebrospinal fluid (CSF) and blood of donors with Parkinson's Disease (PD) 91 . These results suggest that the mitochondrial damage seen in neurodegenerative disorders such as PD 92 and AD 15 is linked to failed regulation of cholinergic targets by CholinotRFs, and potentially to a broader cholinergic and mitochondrial linked defect in sncRNAs at large.…”
Section: Discussionmentioning
confidence: 55%